SOCIO-ECONOMIC CONDITIONS OF THE RICE PADDY FARMERS IN GARAGAHAN VILLAGE LUBUK BASUNG DISTRICT AGAM REGION - DASRI, ALFI; Ahmad, Drs. Ridwan; SE, M.Si, Nefilinda (STKIP PGRI Sumbar, 2014)
ABSTRACTÂ Â Research aimed to get the data, analyze and discuss about the socio-economic conditions of the rice paddy farmers in Garagahan Village Lubuk Basung District of Agam Region view of: level of income, health conditions, and social interactionType of this research is descriptive. Population is the entire rice paddy farmers in Garagahan Village Lubuk Basung District of Agam Region totalling 1082 family. Sample is taken with a proportional random sampling techniques, namely I Bancah Taleh village, II Geragahan Tangah village, III Kampung Caniago village and IV Parit Rantang village with a proportion of 10%, total sample size of rice field rice farmers amounted to 108 heads of families (KK). Data collection using question form of misguided social interactions, analysis used are descriptive statistics using the formula percentages.The results showed as follows; 1) level of income paddy Rice Farmers in Garagahan Village Lubuk Basung District of Agam Region as follows: median income of Rp 2.000.000 â Rp 3,000,000 (58,33%), mean above the UMP Sumatra Barat, mostly farmers also have a side job. Rice paddy farmer spending for food needs (60,19%), and the number of dependents 2 person, (2) health conditions paddy rice farmers the average is close to the level of 2.80 70,4% respondents who are on good enough criteria and (3) average is 3.0 social interaction to the level close to 76.1% of respondents in the criteria is good enough